2010
DOI: 10.1055/s-0037-1619105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of PAR1, GPIb-IX-V, and integrin αIIbβ3 levels in cord and adult platelets

Abstract: A lower content of PAR1-receptors explains very well the hyposensitivity of cord platelets to thrombin. Higher levels of CD42b may additionally support the effect of larger more adhesive multimeric vWF in newborn plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Platelet activation by TRAP resulted in marginal increases in P-selectin expression and PNA formation. This is consistent with other studies showing poor TRAP response of platelets at birth, due to low levels of the protease-activated receptors (PAR-1 and PAR-4) [45, 46]. Platelet responsiveness to TRAP was then observed to improve postnatally with age [24, 25, 46].…”
Section: Discussionsupporting
confidence: 91%
“…Platelet activation by TRAP resulted in marginal increases in P-selectin expression and PNA formation. This is consistent with other studies showing poor TRAP response of platelets at birth, due to low levels of the protease-activated receptors (PAR-1 and PAR-4) [45, 46]. Platelet responsiveness to TRAP was then observed to improve postnatally with age [24, 25, 46].…”
Section: Discussionsupporting
confidence: 91%
“…For platelet-expressed adhesion receptors, Schlagenhauf et al reported higher GPIba levels in term newborn platelet lysates isolated from human cord blood. 12 Earlier studies, including data from the same group, found similar receptor numbers for GPIb on platelets in human neonates and adults. 13,14 More recently, surface levels of GPIba and GPIbb were measured by flow cytometry in mouse samples of different gestational ages, revealing reduced levels of GPIb in fetal platelets compared with adults.…”
Section: Surface Expression Of Adhesion Relevant Moleculesmentioning
confidence: 91%
“…17 Similarly, the investigators of that study reported reduced levels of GPIIb/IIIa in neonatal vs adult platelets, whereas other investigators described equal amounts of GPIIb/IIIa in term newborns compared with adults. 12,15,17 We investigated GPIIb/IIIa expression in mouse fetuses and found an overall increase in GPIIb expression at embryonic day (E)13.5 (of 21 days' gestation) compared with later time points. 3…”
Section: Surface Expression Of Adhesion Relevant Moleculesmentioning
confidence: 99%
“…12 Recently, decreased expression of PAR-1 and PAR-4 receptors was described in neonatal platelets, thus explaining the decreased response to thrombin. 16,17 While this platelet hyporeactivity would have been expected to result in a bleeding tendency, Andrew et al . in 1999 reported that full term neonates had shorter bleeding times (BTs) than healthy adults.…”
Section: Primary Hemostasis In the Neonatementioning
confidence: 99%